2010
DOI: 10.2174/138161210789941883
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Apoptosis in Cancer Development and Treatment: Focusing on the Development and Treatment of Hematologic Malignancies

Abstract: Apoptosis is a normal aspect of human physiology ensuring tissue homeostasis. Evasion of endogenous cell death processes, including apoptosis, represents one of the characteristics of cancer. Defects in the physiological mechanisms of apoptosis contribute to the pathological cell expansion and to the development and progression of cancer. Resistance of malignant cells to cancer therapeutic agents may be, in some cases, caused by dysregulation of apoptotic pathways, e.g. BCL2 or IAP overexpression. The understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 0 publications
0
21
0
5
Order By: Relevance
“…In this process, the plasma membrane remains whole, but undergoes structural alterations, such as the distribution of phosphatidylserine on the outer layer of the membrane, which is a signal for phagocyte recognition 15 . In this manner, the dead cell is quickly removed without leakage of cytoplasmic content, thus avoiding an intense inflammatory response 6 .…”
Section: Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…In this process, the plasma membrane remains whole, but undergoes structural alterations, such as the distribution of phosphatidylserine on the outer layer of the membrane, which is a signal for phagocyte recognition 15 . In this manner, the dead cell is quickly removed without leakage of cytoplasmic content, thus avoiding an intense inflammatory response 6 .…”
Section: Apoptosismentioning
confidence: 99%
“…In this process, senescent or damaged cells are eliminated after activation of a cell death program involving participation of pro-apoptotic molecules (Fas, Bax, caspases 2,3,6,7, 8 and 9). Molecule activation causes typical morphological changes, such as cell shrinkage, loss of adhesion to the extracellular matrix and neighboring cells, chromatin condensation, DNA fragmentation and formation of apoptotic bodies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, proteins of the BCL-2 family appear to be suitable targets for therapies in cancer. 13 To this end, it is crucial to identify the molecules that regulate the apoptotic machinery as well as their downstream effectors.Here, we explored how Spi-1 induces resistance to apoptosis in the preleukaemic erythroid progenitors of the Spi-1 transgenic mice. We found that Spi-1 inhibits mitochondrial apoptosis both in vitro and in vivo through transcriptional repression of Bim.…”
mentioning
confidence: 99%
“…Consequently, proteins of the BCL-2 family appear to be suitable targets for therapies in cancer. 13 To this end, it is crucial to identify the molecules that regulate the apoptotic machinery as well as their downstream effectors.…”
mentioning
confidence: 99%